Adult Still's disease: New horizons - E. L. Nasonov; E. Feist (Научно-практическая ревматология, 2021)
Still's disease in children (systemic juvenile idiopathic arthritis - JIA) and adult Still's disease (ASD) are considered as systemic autoinflammatory diseases of unknown etiology, which are based on similar immunopathogenetic mechanisms associated with genetically determined disorders of the mechanisms of innate immunity. ASD was first described 50 years ago by the English rheumatologist Eric George Lapthorne Bywaters. The molecular basis of ASD immunopathogenesis is the activation of innate immunity associated with NLRP3 inflammasome-dependent mechanisms of inflammation, characterized by the overproduction of “pro-inflammatory” cytokines - interleukin (IL) 1 and IL-18, inducing the synthesis of other proinflammatory inflammatory mediators. A review of new data concerning the mechanisms of immunopathology, clinical polymorphism, laboratory biomarkers and the possibilities of ASD pharmacotherapy is presented.Particular attention is paid to the prospects for the use of monoclonal antibodies to IL-1β - canakinumab. The problems associated with the generality of clinical and laboratory disorders, pathogenetic mechanisms and pharmacotherapy of ASD and coronavirus disease 2019 (COVID-19) are considered.